A randomized controlled trial to evaluate the effect of a new skincare regimen on skin barrier function in those with podoconiosis in Ethiopia. (1st November 2017) - Brooks, J.; Ersser, S.J.; Cowdell, F.; Gardiner, E.; Mengistu, A.; Matts, P.J.
Summary: Background: Podoconiosis affects an estimated 3 million people in Ethiopia with a further 19 million at risk. Volcanic soil and pathogens enter skin breaches in the feet causing inflammation, lymphoedema and hyperkeratosis. There is no robust evidence on optimal podoconiosis skincare regimens to improve skin barrier function (SBF). Objectives: To evaluate the effectiveness of a new, low‐cost, evidence‐based intervention to improve SBF in the lower limbs of those with podoconiosis. Methods: A randomized controlled trial (NCT02839772) was conducted over 3 months in two podoconiosis clinics ( n = 193). The intervention comprised 2% (v/v) glycerine added to a reduced volume of soaking water. The control group received the current skincare regimen. Primary outcome measures were transepidermal water loss (TEWL) and stratum corneum hydration (SCH) at four specific sites on the lower limbs. Results: Improvement in SBF was observed in both groups across all measurement sites and time points, although this was significantly greater in the experimental group. TEWL reduced in both groups at all sites. For example, on top of the foot the estimated group difference in TEWL at visit 4 was 1·751 [standard error (SE) = 0·0390] in favour of the experimental group [ t = 3·15, degrees of freedom (df) = 189·58, P = 0·002, 95% confidence interval (CI) 0·066–2·85], indicating a greater reduction in TEWL in the experimental group. Similarly, at the same site the estimated group difference in SCH at visit 4 was −2·041 (SE = 0·572) in favour of the experimental group ( t = −3·56, df = 186·74, P < 0·001, 95% CI −3·16 to −0·91), indicating a greater increase in SCH in the experimental group. There were also significantly greater reductions in odour, number of wounds and largest foot circumference in the experimental vs. the control group. Conclusions: The addition of 2% (v/v) glycerol to a reduced volume (83% reduction) of soaking water significantly improved SBF.